THE ABILITY OF STUDENTS IN FORMULATING SIMPLE SENTENCE INTO COMPLEX SENTENCE OF SMK 1 SONDER DURING THE PANDEMIC ERA - Yolpi Wukungsenggo; Sri Sudaryati (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
ABSTRACT This study aims to describe the ability to convert simple sentences into complex sentences for students of SMK Negeri 1 Sonder in the pandemic era. This research was conducted at SMK Negeri 1 Sonder in class X E students majoring in marketing for the 2020/2021 academic year which consisted of 20 students. The method used in this study is a qualitative descriptive method, which is intended to describe or describe existing phenomena, both natural phenomena or human engineering. Data collection techniques used in this study were observation, interviews and tests. The formula used to analyze the data in this study is a percentage table with the formula: % = n/N x 100. Based on the data management process, the achievements of class X E students majoring in marketing at SMK Negeri 1 Sonder who have the ability to convert simple sentences into complex sentences in the pandemic era amounted to 82.75%. Based on this value, it means that grade X E students of SMK Negeri 1 Sonder are able to convert simple sentences into complex sentences in the pandemic era.